Blended families: what to consider. (2nd May 2022) - Rawstrone, Annette
Abstract : One of the fastest growing family types in Britain is the step family, or 'blended family'. Within five years of going through a separation or divorce, up to half of parents will have remarried, so be reassured that your child is highly likely to know others who are also living in blended families. That said, it is a big transition that your child will need to be supported through.